A micropatterned conductive electrospun nanofiber mesh combined with electrical stimulation for synergistically enhancing differentiation of rat neural stem cells. Issue 13 (9th March 2020) - Yan, Huanhuan; Wang, Yu; Li, Linlong; Zhou, Xiaosong; Shi, Xincui; Wei, Yen; Zhang, Peibiao
Abstract : The micropatterned conductive nanofiber mesh combined with ES effectively facilitates the differentiation of NSCs into neuron and suppresses the formation of astrocytes. Abstract : An effective treatment for spinal cord injury (SCI) remains a severe clinical challenge due to the intrinsically limited regenerative capacity and complex anatomical structure of the spinal cord. The combination of biomaterials, which serve as scaffolds for axonal growth, cells and neurotrophic factors, is an excellent candidate for spinal cord regeneration. Herein, a new micropatterned conductive electrospun nanofiber mesh was constructed with poly{[aniline tetramer methacrylamide]- co -[dopamine methacrylamide]- co -[poly(ethylene glycol) methyl ether methacrylate]}/PCL (PCAT) using a rotation electrospinning technology. The aim was to study the synergistic effects of electrical stimulation (ES) and a micropatterned conductive electrospun nanofiber mesh incorporated with nerve growth factor (NGF) on the differentiation of rat nerve stem cells (NSCs). The hydrophilicity of the conductive nanofiber mesh could be tailored by changing the dopamine (DA) and aniline tetramer (AT) content from 19° to 79°. A favorable electroactivity and conductivity was achieved by the AT segment of PCAT. The as-fabricated micropatterned electrospun nanofiber mesh possessed a regularly aligned valley and ridge structure, and the diameter of the nanofiber was 312 ± 58 nm, while the width of the valley and ridge was measured to be 210 ± 17 μm and 200 ± 16 μm, respectively. The growth and neurite outgrowth of differentiated NSCs were observed along the valley of the micropatterned nanofiber mesh. In addition, the NGF loaded micropatterned conductive electrospun nanofiber mesh combined with ES exhibited the highest cell viability, and effectively facilitated the differentiation of NSCs into neurons and suppressed the formation of astrocytes, thus exhibiting a great application potential for nerve tissue engineering.